Digestibility Of Ingredients In Two Pelleted Diets By Macrobrachium Rosenbergii (De Man) - Chin, Kenneth Sui Sian (1988)
The digestion coefficients of nutrients in two diets containing 30% and 40% protein were evaluated in the Malaysian giant freshwater prawn Macrobrachium rosenbergii. Chromic oxide was used as an internal marker for the evaluation of digestibility. Evaluations were carried out with juvenile and adult prawns including female prawns undergoing three different stages of gonad maturation.The results indicate that the adult prawns were able to digest the nutrients of the ingredients better than the juveniles. In the two diets tested copra cake, wheat flour and soyabean meal were better digested than fish meal and shrimp meal for both juvenile and adult prawns. Copra cake was found to be a good source of lipids (71- 100% ) , carbohydrate (85 - 9 6 % ) and dry matter ( 72 - 9 2% ) as well as a good attractant. Carbohydrate, gross energy and dry matter were very well digested in wheat flour with values of 9 3 - 100%, 86- 95% and 85-97% respectively. Soyabean meal gave good digestion coefficients for protein (84 - 99% ) , lipid (90- 97% ) and carbohydrate (80- 100% ) . The results indicated that copra cake, wheat flour and soyabean meal are good sources of nutrients for M. rosenbergii. No differences in digestibility was observed for the female prawns with green, yellow and orange gonads. This showed that the stage of gonad maturation has no significant effect on digestibility.